KADAR WASIAT (STUDI KOMPARATIF ANTARA IMAM MALIK DAN HUKUM KEWARISAN DALAM ISLAM) - Jasmiati Jasmiati (HUKUMAH: Jurnal Hukum Islam, 2019)
ABSTRACTThis research is written based on the background of Islamic inheritance law which is quoted from the opinion of the scholars of the such as Abu Hanifah, Syafi’i, Hambali, the servant who argues that the testament is valid only within the limit of 1/3 of the inheritance, when there are heirs, if more than 1/3 of property, it requires the permission of all the heirs. If all of them allow, then the will is valid. While Imam Malik argued that it is not allowed to inherit property beyond the maximum limit of the testament, which is 1/3 property, whether there is permission from the heirs or not.